Phase II open label study of the oral vascular endothelial growth factor-receptor inhibitor PTK787/ZK222584 (vatalanib) in adult patients with refractory or relapsed diffuse large B-cell lymphoma. Issue 12 (December 2013) - Brander, Danielle; Rizzieri, David; Gockerman, Jon; Diehl, Louis; Shea, Thomas Charles; Decastro, Carlos; Moore, Joseph O.; Beaven, Anne
Abstract PTK787/ZK222584 (vatalanib), an orally active inhibitor of vascular endothelial growth factor receptors (VEGFRs), was evaluated in this phase II study of 20 patients with relapsed/refractory diffuse large B-cell lymphoma (DLBCL). Patients received once-daily PTK787/ZK222584 at a target dose of 1250 mg. Eighteen patients were evaluable for response: one patient had a complete response (CR), six patients had stable disease but subsequently progressed, 10 patients had progressive disease by three cycles and one subject withdrew before response evaluation. The patient who attained a CR underwent autologous stem cell transplant and remains disease-free 76 months after study completion. There were no grade 4 toxicities. Grade 3 thrombocytopenia occurred in 20% and grade 3 hypertension occurred in 10%. There were no episodes of grade 3 proteinuria. In conclusion, PTK787/ZK222584 was well tolerated in a heavily pretreated population of patients with DLBCL, although its therapeutic potential as a single agent in DLBCL appears limited.